Defect tolerance at various strain rates in elastomeric materials: An experimental investigation. (1st October 2017) - Brighenti, Roberto; Spagnoli, Andrea; Carpinteri, Andrea; Artoni, Federico
Highlights: Failure crack sensitivity in polymers is examined. Experimental failure behaviour of cracked sheets are presented. Different strain rates are considered. Digital image correlation technique is used for displacement and strain measurements. Crack paths at different strain rates are determined experimentally. Abstract: Elastomeric polymers usually show a very low elastic modulus entailing a soft behaviour and a very high deformation capability. This macroscopic behaviour is determined by their microstructure which is characterized by a complex and entangled network of very long linear chains jointed together in some points called cross-links. Because of such a peculiar microstructure, the mechanical response (often time-dependent) of elastomeric polymers to external loads or deformations cannot be described by the classical theories developed for standard materials – such as the ones whose response depends on their crystalline structure (e.g. metal, ceramics, etc.) – since such polymers usually neglect entropic-related effects that are fundamental in highly deformable amorphous materials. In the present paper, the response of elastomeric plates containing a central crack under a tensile strain applied at various rates is experimentally analyzed giving particular emphasis on the observations of the full-field strain maps determined by means of some digital image correlation techniques. Some relaxation tests are performed, and the defect sensitivity of the material is discussed in relation to the applied deformation rate.